The Influence of Interest Rates on Rental Rate in the United States Islamic Home Financing - Jamilu A Salihu, Jamilu; ., . (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to investigate, whether the rental rate is free from the influence of interest rates on Islamic home financing. The study considers some selected macroeconomic variables to analyze the influence of interest rates on the rental rate. The study focuses on the United States data covering from the first quarter of 1990 to the last quarter of 2016. The study adopts Autoregressive distributed lags (ARDL) model to analyze the long-run and short-run relationships between the rental rate and the macroeconomic variables. The study finds consistent evidence that rental rate is free from the influence of short term and long term interest rates in both long-run equilibrium and short-run dynamic results in the United States Islamic home financing. Hence, the rental rate could be accepted as an alternative to interest rates in Islamic home financing. The result contributes towards finding that the rental rate is free from the influence of interest rate in Islamic home financing. To the best of the authorâ€™s knowledge, the present study is the first of its kind which empirically investigates the influence of interest rates on the rental rate in Islamic home financing.Â Â